2013
DOI: 10.7860/jcdr/2013/6040.3136
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Iodine Excretion In Pregnancy: A Pilot Study in The Region of Nepal

Abstract: Background: Pregnancy is accompanied by profound alterations in the thyroid economy and the relative iodine deficiency. The median Urinary Iodine Excretion (UIE) is the most reliable indicator of the population's iodine nutrition. The physiological alterations in normal pregnancy, such as an increased glomerular filtration rate, potentially invalidate UIE as an assessment tool in pregnancy. Objectives:To assess the Urinary Iodine Excretion (UIE) in pregnant mothers and to enquire about the current status of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…Furthermore, the finding of the study is far greater than those of studies conducted in Nepal (28.9%) [ 25 ], and Kolkata (37%) [ 26 , 27 ]. Poor dietary intake of iodine-rich food and low utilization of iodized salt could explain the observed discrepancies.…”
Section: Main Textcontrasting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, the finding of the study is far greater than those of studies conducted in Nepal (28.9%) [ 25 ], and Kolkata (37%) [ 26 , 27 ]. Poor dietary intake of iodine-rich food and low utilization of iodized salt could explain the observed discrepancies.…”
Section: Main Textcontrasting
confidence: 69%
“…Poor dietary intake of iodine-rich food and low utilization of iodized salt could explain the observed discrepancies. As an illustration, iodized salt utilization coverage in Nepal was (66.7%) [ 28 ], which is far better than Ethiopia (23.3%) [ 17 ].…”
Section: Main Textmentioning
confidence: 99%
“…Despite the higher UICs found in the present study than in other Turkish studies, the percentage of pregnant women with inadequate (28.8% versus 28.1%), adequate (37.78% versus 34.1%) and more than adequate (33.3% versus 34.8%) iodine intakes were similar in a study conducted among pregnant women in Nepal. 14 A study of 1322 healthy pregnant women in northern Spain reported a median UIC in the second trimester of 140 µg/L. The study also reported that 54.4% of subjects had iodine deficiency while 18.8% of subjects had higher than recommended UIC.…”
Section: Discussionmentioning
confidence: 97%